Pengaruh Inflasi, Kurs, Produksi Minyak Sawit Terhadap Volume Ekspor Minyak Sawit Di Indonesia Periode 1990-2020 - Rayhan Azam Ramadhana; Syamsul Hadi (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2023)
This study aims to determine the influence exerted by Inflation, Exchange Rates, Palm Oil Production on the Export Volume of Indonesian Palm Oil for the period 1990-2020. The data used is secondary data obtained from Bank Indonesia, the Directorate General of Plantations and the Oil Palm Statistics Agency. This study uses time series data analysis with the Multiple Linear Regression method. The results of this study indicate that inflation, exchange rates and palm oil production have a significant effect on Indonesian palm oil exports. Partially, the inflation variable has a negative and significant influence on Indonesian palm oil exports. Partially, the production variable has a positive and significant effect on exports of Indonesian palm oil commodities. The Rupiah exchange rate shows a positive and significant effect on Indonesian palm oil exports.